Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter R - Section R.3 - Exponents, Roots, and Order of Operations - R.3 Exercises: 22

Answer

True.

Work Step by Step

It's true that $(-a)^n=-a^n$ if $n$ is odd and $a$ is a positive integer because: $(-a)^n=(-1*a)^n=(-1)^n(a)^n=-1a^n=-a^n$ (we know that $(-1)^n=-1$ if $n$ is odd.)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.